Gyrokinetic Simulation of Magnetic Compressional Modes in General Geometry (Communications in Computational Physics, 2011)
A method for gyrokinetic simulation of low frequency (lower than the cyclotronfrequency) magnetic compressional modes in general geometry is presented.The gyrokinetic-Maxwell system of equations is expressed fully in terms of the compressionalcomponent of the magnetic perturbation, δB‖, with finite Larmor radius effects.This introduces a "gyro-surface" averaging of δB‖ in the gyrocenter equations ofmotion, and similarly in the perpendicular Ampere's law, which takes the form of theperpendicular force balance equation. The resulting system can be numerically implementedby representing the gyro-surface averaging by a discrete sum in the configurationspace. For the typical wavelength of interest (on the order of the gyroradius), thegyro-surface averaging can be reduced to averaging along an effective gyro-orbit. Thephase space integration in the force balance equation can be approximated by summingover carefully chosen samples in the magnetic moment coordinate, allowing foran efficient numerical implementation.